Effect of interfibrillar PVA bridging on water stability and mechanical properties of TEMPO/NaClO2 oxidized cellulosic nanofibril films. (1st August 2015) - Hakalahti, Minna; Salminen, Arto; Seppälä, Jukka; Tammelin, Tekla; Hänninen, Tuomas
Highlights: Water stable films from TEMPO/NaClO2 oxidized CNF and PVA were produced. Method involved a simple solvent-casting method without any post-treatments. Properties of films could be tuned by adjusting the amount of PVA. Poly(vinyl alcohol) functioned as a reinforcing agent and a plasticizer in films. Abstract: TEMPO/NaClO2 oxidized cellulosic nanofibrils (TCNF) were covalently bonded with poly(vinyl alcohol) (PVA) to render water stable films. Pure TCNF films and TCNF–PVA films in dry state showed similar humidity dependent behavior in the elastic region. However, in wet films PVA had a significant effect on stability and mechanical characteristics of the films. When soaked in water, pure TCNF films exhibited strong swelling behavior and poor wet strength, whereas covalently bridged TCNF–PVA composite films remained intact and could easily be handled even after 24 h of soaking. Wet tensile strength of the films was considerably enhanced with only 10 wt% PVA addition. At 25% PVA concentration wet tensile strengths were decreased and films were more yielding. This behavior is attributed to the ability of PVA to reinforce and plasticize TCNF-based films. The developed approach is a simple and straightforward method to produce TCNF films that are stable in wet conditions.